Электроны цикл хурдасгуур микротрон МТ-22 - Д, Баатархүү; А.Г, Белов; П.Г, Бондаренко; Ш, Гэрбиш; С, Даваа; Б, Далхсүрэн; Н, Норов; Ч, Намнан; Б, Отгоолой; Н, Содном; Б, Сэргэлэн; Г, Хүүхэнхүү; et al. (Scientific transaction of the National University of Mongolia. Physics, 2022)
Technical and physics characteristics of the Microtron MT-22 operating at the Nuclear Research Centre of the National University of Mongolia are presented.